Implementasi Konsep Regeneration dalam Perancangan Interior Floral Community and Eco Tourism Centre - Cindy Tanara; Diana Thamrin; Linggajaya Suryanata (Intra, 2019)
IPBI (Ikatan Perangkai Bunga Indonesia) community is a community which embraces all flower lovers in Indonesia, but unfortunately this community does not have a permanent place to carry out the community activities. The purpose of this design is to provide a forum to meet the needs of socialization and recreation for flower lovers and optimize activities between IPBI community members. The design method used in this design consists of the stages of Understand, Observe, Point of View, Ideate, Prototype, and Test. The result of this design is an Interior Design for Floral Community and Eco Tourism Center with the concept of Regeneration. Interior elements and furnishings are designed to stimulate flower lovers, especially the millennial generation, to socialize, coordinate and enjoy together. The design goals are expected to form a pattern of activities that are beneficial for flower lovers in Surabaya.